Climate change adaptation strategies, food security and gender relations: A case of pastoralists in Kilosa District, Tanzania - Mushi, Venosa (Mzumbe University, 2023)
This manuscript assesses how pastoralists adapt to climate change in achieving food security, with respect to the existing gender power relations in Tanzania. Although various studies have been conducted on climate change and gender, information with a strong focus on climate change adaptation strategies, food security and gender power relations, particularly in Tanzania, is scarce. To fill the information gap, both primary and secondary data were collected through a cross-sectional research design from 50 respondents, complemented with a desk review of various documents on gender, climate change adaptation strategies and food security. Questionnaire administration, in-depth interviews and focus group discussions were used as data-collection methods. Quantitative data were analyzed by the use of IBM SPSS Statistics computer program version 22, while qualitative data were analyzed through content analysis. Results show that 32 BOOK OF ABSTRACTS inequality in gender–power relations exists among the pastoralists in terms of ownership of resources and decision-making. The findings further revealed that the respondents use various strategies to adapt to climate change as remedy to sustainable food security. The findings of this study are expected to contribute to the existing body of knowledge on gender–power relations and climate change adaptation, thus informing policy planners/makers who are interested in formulating relevant climate change adaptation policies with a gender perspective/lens. Thus, gender-sensitive policies and strategies on ownership of resources and decision-making at the household level are required to trim down women’s vulnerability to climate change impacts and food insecurity at large. The government should also design implementable policies to ensure sustainable food security.